Conflitos sociambientais urbanos: o caso da revitalização de igarapés da cidade de Manaus - Azevedo, Renildo Viana (2008)
The social-environmental conflicts are an urban "new" type of social conflict, originates from the ownership of the environmental discourse by governmental agencies and various stakeholders, as an argument for protection and promotion of the interests that are at stake. The plans of action and intervention promoted by governmental agencies to preserve and protect the environment come into conflict with the interests of parts of the population, usually taken by governmental agencies as causing environmental degradation of the affected areas. Conflicts resulting from this process represent a new component of a struggle for the city. In this case, the environmental law is exerting a major role in formulating concepts and legal standards capable of creating realities and of imposing design of a city. Due to the ownership of the environmental discourse by the state and various social agents, it is possible to relativize the notion of universal respect for the environment, where everyone would be interested in protecting. From the study of urban intervention of the State Government in streams of Manaus, seeks to examine the role of law in the development of this process, where you can watch the raising of environmental separate speeches, which are antagonized by explaining the conflict living there. Keywords: Social-environment Conflicts, Law, Revitalization, “Igarapés”